Larvicidal effect of dried leaf extracts from Pinus caribaea against Aedes aegypti (Linnaeus, 1762) (Diptera: Culicidae) - Kanis,Luiz Alberto (2009)
In this study, the larvicidal activity of dried leaf extracts from Pinus caribaea Morelet against Aedes aegypti was evaluated for the first time. Pinus caribaea extracts were obtained by macerating dried leaves in alkaline hydroethanol, ethanol and acetone solutions followed by evaporation under reduced pressure. The lignin content was quantified using the thioglycolic acid complexation method. Lethality bioassays (LC50 and LC90) were carried out in accordance with the recommendations of the World Health Organization. The results showed that the acetone extract from Pinus caribaea was more active, and that larvicidal activity was associated with lignin concentration.